2019
DOI: 10.1038/s41598-019-53445-2
|View full text |Cite|
|
Sign up to set email alerts
|

An exome-wide rare variant analysis of Korean men identifies three novel genes predisposing to prostate cancer

Abstract: Since prostate cancer is highly heritable, common variants associated with prostate cancer have been studied in various populations, including those in Korea. However, rare and low-frequency variants have a significant influence on the heritability of the disease. The contributions of rare variants to prostate cancer susceptibility have not yet been systematically evaluated in a Korean population. In this work, we present a large-scale exome-wide rare variant analysis of 7,258 individuals (985 cases with prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…As is known, the short arm of chromosome 3 is the most important region contributing to the pathogenesis of RCC, for the reason that several tumor suppressor genes, like VHL, SETD2, and PBRM1, are identified within this region [ 26 ]. ENTPD3-AS1 was reported to be significantly associated with prostate cancer [ 27 ]. A locus (rs193921050) in ENTPD3-AS1 has been reported for “malignant tumor of the prostate” in ClinVar with uncertain clinical significance [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…As is known, the short arm of chromosome 3 is the most important region contributing to the pathogenesis of RCC, for the reason that several tumor suppressor genes, like VHL, SETD2, and PBRM1, are identified within this region [ 26 ]. ENTPD3-AS1 was reported to be significantly associated with prostate cancer [ 27 ]. A locus (rs193921050) in ENTPD3-AS1 has been reported for “malignant tumor of the prostate” in ClinVar with uncertain clinical significance [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its research methods are used for mining and understanding the biological significance contained in massive data through various technologies and tools of computer science, biology and mathematics [ 44 ]. Many studies have shown that bioinformatics-based DNA methylation analysis is widely used for the identification of multiple human diseases, malignant tumor diagnosis, biomarker screening and targeted therapy [ 45 , 46 , 47 , 48 , 49 , 50 ]. The gold-standard method for quantitative interrogation of the methylation state of all CpG dinucleotides in a genome is Whole-Genome Bisulfite Sequencing (WGBS) [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs can serve as competing endogenous RNA (ceRNA) to regulate gene expression by competitively binding miRNAs [19]. ENTPD3-AS1 has been reported to be associated with prostate cancer susceptibility [20]. In contrast, ENTPD3-AS1 has also been regarded as a tumor suppressor in renal cell carcinoma by inhibiting miR-155/HIF axis [21].…”
Section: Discussionmentioning
confidence: 99%